2019
DOI: 10.1111/jch.13737
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the causal link between homocysteine and hypertension from a meta‐analysis of 40 173 individuals implementing Mendelian randomization

Abstract: Numerous researchers have investigated the associations among methylenetetrahydrofolate reductase gene (MTHFR) C677T polymorphism, homocysteine (Hcy) concentration, and hypertension. However, the results are controversial. Thus, a meta‐analysis implementing Mendelian randomization approach was conducted to examine the hypothesis that elevated Hcy concentration plausibly contributes to increased risk of hypertension. Based on several inclusion and exclusion criteria, eligible studies were selected to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 104 publications
5
34
0
Order By: Relevance
“…Previous studies found that HCY is another major risk factor for cerebrovascular disease in addition to hypertension. A meta-analysis also found that hypertension was closely associated with HCY and there is a direct interaction between hypertension and HCY [14]. In our study, the median value of HCY in H-type hypertension group was 14.25μmol/L (interquartile range of 12.23 to 18.37μmol/L).…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies found that HCY is another major risk factor for cerebrovascular disease in addition to hypertension. A meta-analysis also found that hypertension was closely associated with HCY and there is a direct interaction between hypertension and HCY [14]. In our study, the median value of HCY in H-type hypertension group was 14.25μmol/L (interquartile range of 12.23 to 18.37μmol/L).…”
Section: Discussionsupporting
confidence: 67%
“…A meta-analysis had identi ed potentially relevant researches up to August 1, 2019. The conclusion was that hypertension was closely associated with HCY [9]. According to previous ndings, a high level of HCY did harm to systemic vascular endothelial cells [10,11].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies found that HCY is another major risk factor for cerebrovascular disease in addition to hypertension. A meta-analysis also found that hypertension was closely associated with HCY, and there is a direct interaction between hypertension and HCY [ 14 ]. In our study, the median value of HCY in H-type hypertension group was 14.25 µmol/L (interquartile range, 12.23 to 18.37 µmol/L).…”
Section: Discussionmentioning
confidence: 99%